Post-Digital, Post-Internet Art and Education The Future is All-Over - Tavin, Kevin; Kolb, Gila; Tervo, Juuso (Palgrave Studies in Educational Futures, 2021)
This open access edited volume provides theoretical, practical, and historical perspectives on art and education in a post-digital, post-internet era. Recently, these terms have been attached to artworks, artists, exhibitions, and educational practices that deal with the relationships between online and offline, digital and physical, and material and immaterial. By taking the current socio-technological conditions of the post-digital and the post-internet seriously, contributors challenge fixed narratives and field-specific ownership of these terms, as well as explore their potential and possible shortcomings when discussing art and education. Chapters also recognize historical forebears of digital art and education while critically assessing art, media, and other realms of engagement. This book encourages readers to explore what kind of educational futures might a post-digital, post-internet era engender.